Humor Nabi: Kajian Tematik Hadis tentang Canda Rasulullah: The Humor of the Prophet: A Thematic Hadith Study on the Messenger's Jesting - Nurul Iffatiz Zahroh; Muhammad Abdul Kharis; Zulfa Rizal (AL ISNAD: Journal of Indonesian Hadith Studies, 2026)
Humor and jesting constitute an inherent aspect of human life as social beings, including in the daily practices of Nabi Muhammad. Nevertheless, the understanding of humor in Islam is often perceived in a partial manner and is at times regarded as being at odds with the values of seriousness and piety. Therefore, a comprehensive study grounded in authoritative sources is necessary to understand how Islam, through the example of the Prophet, positions humor within human life. This article aims to examine the forms, contexts, and underlying values of the Prophet’s humor and laughter from the perspective of hadith. The methodology used is a qualitative approach with a thematic method towards the hadiths narrated in the hadith books and sīrah nabawiyyah. The analysis is conducted by considering the context of transmission, textual meanings, and the ethical implications embedded within each narration. The findings reveal that the Prophet’s humor was consistently grounded in truthfulness, gentleness, and educational purpose. His jesting never involved falsehood, mockery, or humiliation; rather, it functioned as a medium of da‘wah and a means of strengthening emotional bonds between him and his companions. This study demonstrates that humor in Islam, as exemplified by the Prophet, is not merely a form of entertainment, but also a reflection of noble character that harmonizes spiritual seriousness with human cheerfulness.